Prenatal Development of Efferent Ductules in Indian Buffalo (Bubalus bubalis) - Sharma, Anil; Bansal, Neelam; Uppal, Varinder (Indian Journal of Veterinary Anatomy, 2012)
The present study was conducted on thirty buffalo foetii ranging from 3 to 98 cm CVRL. The efferent ductules appeared as small, luminized and non-luminized set of secondary mesonephric tubules on the dorsal aspect of mesonephric giant corpuscle in buffalo foetii of 9 cm CVRL (69 days). Number and size of efferent ductules increased at 17 cm CVRL (105 days) onwards. Coiling of efferent ductules was observed at 17 cm CVRL and the lobulation was observed at 23 cm CVRL (127 days). The lining epithelium of efferent ductules was low columnar type at 9 to 13.7 cm CVRL (69 to 90 days) which was transformed into simple columnar epithelium having ciliated and non-ciliated cells at 17 cm CVRL (105 days). The typical syncytium of mesenchymal tissue surrounding the efferent ductules was observed at 9 cm CVRL (69 days) which later on condensed to form the peritubular cells.